Molecular and serological evidence of chikungunya virus among dengue suspected patients in Sri Lanka - Mya Myat Ngwe Tun; Maurine Mumo Mutua; Shingo Inoue; Yuki Takamatsu; Satoshi Kaneko; Takeshi Urano; Rohitha Muthugala; Lakkumar Fernando; Menaka Hapugoda; YINS Gunawardene; Kouichi Morita (Journal of Infection and Public Health)
Background: Chikungunya virus (CHIKV), transmitted by Aedes mosquitoes, causes significant morbidity characterized by acute febrile illness to chronic and permanent disability in some patients. Despite its potential for severe long-term effects, surveillance for CHIKV remains limited, especially in dengue-endemic region like Sri Lanka. To address the gap in surveillance, this study aimed to determine the prevalence of CHIKV among patients suspected of dengue fever during the 2017–2019 DENV outbreak in Sri Lanka. Methods: Serum samples were collected from 295 patients at Kandy National Hospital and 300 patients at Negombo Hospitals, presenting with dengue-like symptoms such as fever, rash, and arthralgia. We performed quantitative real-time RT-PCR (RT-qPCR) to detect the CHIKV genome and conducted serological tests for anti-CHIKV IgM and IgG antibodies on all samples. Serology-positive samples were further validated with neutralization assays to confirm CHIKV-specific antibodies. Results: The prevalence of recent CHIKV infection (IgM or RT-qPCR positive) was 2.4 % and 7.0 %, while past CHIKV infection (IgG-positive) was 16.3 % and 12.3 % with neutralizing antibody (NAb) in Kandy and Negombo Hospitals, respectively. All IgG-positive samples exhibited NAb with titers of 10 or higher. The NAb geometric mean titer in the Kandy and Negombo areas does not show a significant difference. In the Kandy area, the majority of CHIKV infections occurred in young adults aged 13–24 years, accounting for 57.1 % of recent infections and 52.1 % of past infections. Conclusion: CHIKV circulates alongside DENV outbreaks, with a higher prevalence of recent infections in Negombo compared to Kandy, while past infections are more common in Kandy than in Negombo. Neutralization assays confirmed the presence of CHIKV-specific antibodies, emphasizing the need for enhanced surveillance for proper patient care and management. These findings underscore the importance of public health interventions, including surveillance programs and vaccine development, to mitigate the burden of CHIKV in Sri Lanka.